(untitled) (The Journal of Forensic Accounting Profession, 2022)
Public procurement system, which is being implemented in Bosnia and Herzegovina, is an integrated system that includes a large number of actors. This system is described, including the identified competencies and responsibilities of all participants, by law and bylaws. And, corruption is one of the social phenomena whose definitions change in time and space. Many behaviors that are considered corruption today have been an integral part of regular behavior in the past. (Previously published on Sciendo: https://sciendo.com/article/10.2478/jfap-2022-0003, pod licencom CC BY-NC-ND 4.0)